2022
DOI: 10.1002/ldr.4170
|View full text |Cite
|
Sign up to set email alerts
|

Soil and water conservation in terraced and non‐terraced cultivations: an extensive comparison of 50 vineyards

Abstract: Understanding the soil and water conservation (SWC) impact of steep-slope agricultural practices (e.g. terraces) has arguably never been more relevant than today, in the face of widespread intensifying rainfall conditions. In Italy, a diverse mosaic of terraced and non-terraced cultivation systems have historically developed from local traditions and more recently from the introduction of machinery. Previous studies suggested that each type of vineyard configuration is characterised by a specific set of soil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
(83 reference statements)
0
9
0
1
Order By: Relevance
“…However, it is important to note that especially in semi-arid regions, where vineyards or olive plantations are typically found, cover crops compete with the orchard crops for water and in a best case the prevention of surface runoff should offset additional transpiration losses (Ruiz-Colmenero et al, 2011). As this is difficult to achieve, best soil conservation effects, especially in steep vineyards, are often reached with measures as contour terracing (Pijl et al, 2022).…”
Section: Agriculture and Erosionmentioning
confidence: 99%
“…However, it is important to note that especially in semi-arid regions, where vineyards or olive plantations are typically found, cover crops compete with the orchard crops for water and in a best case the prevention of surface runoff should offset additional transpiration losses (Ruiz-Colmenero et al, 2011). As this is difficult to achieve, best soil conservation effects, especially in steep vineyards, are often reached with measures as contour terracing (Pijl et al, 2022).…”
Section: Agriculture and Erosionmentioning
confidence: 99%
“…The survey of vineyards' soil erosion has been receiving more attention since the beginning of the 21st century based on different methodologies: rainfall simulations [45], runoff and sediment plots [46], topographical measurements [47] and modelling [48]. Within that research perspective, the study of the connectivity of water and sediments in vineyards has been a key topic to understand the mechanism of sediment transport [29,49]. Measurements of the solutes have been rare in vineyards and our research is pioneering.…”
Section: Further Researchmentioning
confidence: 99%
“…Most of the respondents (79.6%) reported problems with management of terraced vineyards (question 20). As shown in Table 6, the main problems in the management of terraced vineyards reported by winegrowers were terraces management and accessibility (cited 12 and 11 times, respectively), followed by poor mechanization (7), difficulty with management (5), and water availability (5). Problems cited less frequently were proximity to uncultivated lands (2), too much time for cultivation (2), land pulverization (2), management costs (2), too much time for pergola vine-breeding technique management (1), and pilun management (1).…”
Section: Evaluation Of Winegrowers' Perceptionsmentioning
confidence: 99%
“…These anthropogenic soils were classified by Freppaz et al [6] as Technic Cambisols (Escalic). Pijl et al [7] observed the responses of different practices on steep slopes in Italy to extreme rainfall events and found that terracing practices were characterized by better mitigation of sediment flux than nonterracing practices. Along the same lines, recent research conducted in Morocco showed the important capability of agricultural terraces of increasing water infiltration and their important role in flood protection and runoff mitigation [8].…”
Section: Introduction 1terraced Landscapes and Rural Communitiesmentioning
confidence: 99%